Stress Response and Pathology of Hybrid Groupers (Epinephelus lanceolatus × Epinephelus fuscoguttatus) Infested Trichodina sp. Maintained in Hatchery from Bali, Indonesia - Lia Oktavia Ika Putri; Gunanti Mahasri; Ahmad Shofy Mubarak; Lilis Cahaya Septiana (Journal of Aquaculture Science, 2025)
The demand for grouper fish continues to increase, with the Ministry of Fisheries' annual production target of 9,000 tons. However, intensive cultivation systems pose risks due to poor water quality, making grouper fish susceptible to disease and health problems. This study investigated the impact of Trichodina sp. infection on the blood glucose levels of hybrid grouper fish. The study was conducted in May 2024 by observing 30 fish and measuring blood glucose. The results showed that 20 fish showed glucose levels above the normal range (> 57.6 mg/dL), ranging from 61 to 114 mg/dL. In contrast, nine fish had glucose levels in the normal range (28.8 - 57.5 mg/dL), and one fish had low glucose levels of 26.7 mg/dL. High glucose levels in most fish indicate stress or metabolic disorders, possibly related to Trichodina sp. infestation. This parasitic infection can compromise the fish's immune system, making the fish more susceptible to disease. The results emphasize the need for effective parasite management and optimal water quality in intensive culture systems. To maintain grouper health and productivity, it is important to monitor water quality, control ectoparasites, and conduct further research on the long-term effects of these infections on blood glucose and overall health.